Douglas' solution of the Plateau problem - Guillemin, Victor (1988)
Using ideas suggested by some recent developments in string theory, we give here an elementary demonstration of one of the key steps in Douglas' celebrated proof of the existence of solutions of the Plateau problem in n dimensions.